796 Return to work among self-employed cancer survivors: a european comparative study. (24th April 2018) - Torp, S; Paraponaris, A; Hoof, EV; Lindbohm, ML; Tamminga, SJ; Alleaume, C; Gavin, AT; Campenhout, NV; de Boer, AGEM; Sharp, L
Abstract : Introduction: Studies on cancer survivors' (CS) return to work (RTW) after cancer have mostly focused on salaried workers. RTW among self-employed CS has almost not been focused although there are big differences in these two groups' working conditions and social welfare provisions. The aim of this study is therefore to bring together data from multiple European countries to: describe RTW–related outcomes after cancer in self–employed people; compare these outcomes for the self–employed with those for salaried workers; and describe RTW–related outcomes after cancer for self–employed people across countries. Methods: Eleven cross-sectional studies from seven countries were included. All studies had survey data on work-outcomes in self-employed and salaried CS who were employed at time of diagnosis (n=22–261 self-employed/101–1627 salaried). The studies included different cancers and assessed different outcomes at different times post-diagnosis. Results: Fewer self-employed CS took time off work due to cancer compared to salaried survivors. More self-employed than salaried worked post-diagnosis in almost all countries. Among those working at the time of survey, self-employed survivors had made a larger reduction in working hours compared to pre-diagnosis, but they still worked more hours per week post-diagnosis than salaried survivors. The self-employed had received less financial compensation when absent from work post-cancer, and more self-employed, than salaried, survivors reported a negative financial change due to the cancer. There were differences between self-employed and salaried survivors in physical job demands, work ability and quality-of-life but the direction and magnitude of the differences differed across countries. Discussion: Self-employed and salaried CS differ when it comes to RTW-related outcomes, but the patterns vary between countries. Support should be provides to self-employed survivors to help them balance their health needs with those of their business.